Comparative Performance Analysis of Conventional and Islamic Banks in Nigeria Using Camel Rating Model - Umar, Manir; sayudin, sayudin (Riviera Publishing, 2024)
This study examines financial performance of Conventional and Islamic banking in Nigeria using CAMEL rating model covering the period of 2012-2022. Secondary sources of data were collected from the bank’s financial statements. The study adopted an ex-post facto research design and purposive sampling technique to select the sampled banks for the study. Two banks Jaiz Bank Plc and Unity Bank Plc (both from Conventional and Islamic banks) were drowned to serve as the study sample. Descriptive and inferential statistics was used as tool of analysis to show the trends of performance (CAMEL) between the two banks using mean, minimum, maximum and standard deviation and also to check the relationship between the variables. Further, in inferential statistics, t-test was used to compare and test the significant variation between CAMEL components of the banks. The results showed the existence of low and negative trends in the quality of earnings of both banks. It also showed trends of performance between the two banks are significantly affected by all the CAMEL components. Moreover, results from t-tests showed a significant variation of three CAMEL components and the acceptance of alternative hypothesis. The study recommended the management of both bank should put more effort to mitigate the negative return volatility of the banks. Both bank need to have strong liquid-based or near liquid e.g., short-term securities (government bonds). A lot more effort needs to be made to create value-based products.